Repositioning of the Barrio del Artista to increase its cultural-artistic value in Puebla, Mexico - Acle-Mena, Ramón Sebastián; Villalobos-Abrego, Carolina; Herrera-López, Beatriz (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The main aim of the current study was to identify the correlation of the Barrio del Artista repositioning to enhance its artistic and cultural value in Puebla city, Mexico. The research was conducted within a marketing focus. The presented results correspond to an empirical research on the repositioning of the Barrio del Artista, using a quantitative approach and Pearson’s correlation coefficient, making the application of the factors that compose positioning to determine the relationship between the Barrio del Artista repositioning and the increase of its artistic and cultural value in Puebla city. For this research, the novel concepts of marketing and positioning were used in a practical way.